1964
DOI: 10.1128/aem.12.5.412-417.1964
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Ecology of Activated Sludge

Abstract: Over 300 bacterial strains were isolated from seven samples of activated sludge by plating on sewage agar. Gram-negative bacteria of the genera Zoogloea and Comamonas predominated. Many isolates (51%) showed sudanophilic inclusions of poly-,3-hydroxybutyric acid, whereas 34% accumulated iodophilic material on media containing starch. A large number required either vitamins or amino acids, or both, for growth. None of the isolates tested for their ability to bring about changes in autoclaved sewage produced an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
1

Year Published

1969
1969
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…Continuously stirred tank reactors (CSTRs) are commonly used in biological treatment of industrial wastewaters and there have been many laboratory and pilot-scale studies to study biodegradation kinetics in CSTRs. In continuous studies conducted with heterogenous microbial populations many investigators have observed population dynamics (Andrews and Pearson, 1965;Bower and Gaddis, 1968;CasselzyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA el at., 1966;Chian and Mateles, 1968;Collard and Gossling, 1967;Dias and Bhat, 1964;Downing and Wheatland, 1962;Jannasch, 1965;Jannasch, 1967;Milbury and Pipes, 1965;and Prakasam and Dondero, 1965). It has been reported by Jannasch (1965), Collard and Gossling (1967), Chian and Mateles (1968), Mateles ( 1967), and Dias and Bhat (1964) that in mixed continuous cultures, Escheria coli, Streptococcus fecalis, Bacteroides spp., Nocardia albicans, Staphylococcus albus, Achromobacter spp., and others dominated at lower dilution rates whereas species belonging to genus Pseudomonas were dominant at higher dilution rates when the former species were selected against.…”
mentioning
confidence: 95%
“…Continuously stirred tank reactors (CSTRs) are commonly used in biological treatment of industrial wastewaters and there have been many laboratory and pilot-scale studies to study biodegradation kinetics in CSTRs. In continuous studies conducted with heterogenous microbial populations many investigators have observed population dynamics (Andrews and Pearson, 1965;Bower and Gaddis, 1968;CasselzyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA el at., 1966;Chian and Mateles, 1968;Collard and Gossling, 1967;Dias and Bhat, 1964;Downing and Wheatland, 1962;Jannasch, 1965;Jannasch, 1967;Milbury and Pipes, 1965;and Prakasam and Dondero, 1965). It has been reported by Jannasch (1965), Collard and Gossling (1967), Chian and Mateles (1968), Mateles ( 1967), and Dias and Bhat (1964) that in mixed continuous cultures, Escheria coli, Streptococcus fecalis, Bacteroides spp., Nocardia albicans, Staphylococcus albus, Achromobacter spp., and others dominated at lower dilution rates whereas species belonging to genus Pseudomonas were dominant at higher dilution rates when the former species were selected against.…”
mentioning
confidence: 95%
“…The contribution made by the coryneforms is an enigma, it may be that they comprise a4 associated group dependent for their development on the dominant organisms yet they do not conform to the general shape and arrangement of the organisms detected by microscopic examination of the film. (Dias & Bhat, 1964;van Gils, 1964) the flora has been dominated by an association between achromobacters (Achromobacter and/or Alcaligenes) and Fluvobacterium. The dominant flora described in this investigation (an association between Acinetobacter and yellow-pigmented Gram negative rods) may be considered to resemble one dominated by achromobacters and flavobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Using a homogenization technique to investigate activated sludge, Allen (1944) identified the majority of organisms with Achromobacter, Fluvobacterium or Pseudomom. I n subsequent studies of activated sludge (McKinney & Weichlein, 1953 ;Jasewicz & Porges, 1956;Rogovskaya & Lazareva, 1959;Dias & Bhat, 1964;Van ails, 1964;Adamse, 1966) and trickling filters (James, 1964) these organisms together with Zoogloea, Cornamonas, Alculigenes and coryneforms have been described as dominant whilst a great many other organisms have been noted also. However, identification of a bacterial isolate is achieved by comparison with named types described in treatises on determinative bacteriology and the current definitions tend in many instances to differ from those of earlier usage.…”
mentioning
confidence: 99%
“…Many of the bacteria present cannot be cultured, because of either undetermined nutritional requirements or the inability to grow as colonies on solid media (19). Even so, a number of studies have been done and numerous genera have been identified within sludge-forming bacterial populations (4,11,18).…”
mentioning
confidence: 99%